A review of mangrove value and conservation strategy by local communities in Hormozgan province, Iran - Ghasemi, Saber; Hussin, Mohamed Zakaria; Abdul Hamid, Hazandy; Yusof, Ebil; Danehkar, Afshin; Rajpar, Muhammad Nawaz (Marsland Press, 2010)
Mangroves are forest community within the intertidal region of tropical and subtropical areas. This study provides the values, functions and attributes of mangrove ecosystem and the importance of the local people in biodiversity conservation in the mangrove of Gas and Hara Rivers Delta (GHRD) in the Iranian coastline of Oman Sea. This study indicated that mangroves of GHRD are greatly influenced by the coastal environment and fulfil important socio-economic and environmental functions, therefore, it is considered that the protection of this site from threats must be enfaced. This study also provides the state of key guidelines for protecting biodiversity of mangroves by the local people. Over-use, lack of identity of mangrove resource and lack of tools for mangrove economic evaluation are the main destruction factors of the mangrove in this region. This study suggested that the end goal is to involve communities in direct management of resources. Furthermore, this study highlighted the role of awareness-raising in local communities in GHRD biodiversity conservation. There should be a willingness to move from old ideas on the use of this natural resource by villager and other people, which are largely dependent on this ecosystem. Awareness-raising campaigns must be developed for local communities using local languages, religious leaders and cultural events.